THE ROLE OF THE TOURIST INFORMATION CENTER (TIC) OF SOEKARNO HATTA AIRPORT IN THE CHOICE OF TOURIST DESTINATIONS BASED ON TOURIST CHARACTERISTICS AND SERVICES - Setiawan, Agung; Munandar, Jono M.; Sarma, Ma’mun (Universitas Brawijaya, Indonesia, 2020)
Tourist destination information is an important element in tourism promotion and marketing. The need for tourism facilities that can respond to problems related to the availability of tourism information and at the same time play a role in tourism promotion and marketing activities of a tourist destination requires the presence of a Tourism Information Center/TIC. Tourist Information Center (TIC) activities are service activities with the core being the delivery of tourist information. This research is exploring the three previous research conducted by Brady Cronin (2001), Gronroos (2000), and King (1987), which aims to investigate the optimization of TIC services. Sampling in this study was 175 respondents. Data processing uses SPSS and Structural Equation Modeling (SEM) AMOS 24. Service users were predominantly male, with an age range of 26-35 years, and the majority of undergraduate education, occupational status was dominated by private employees. While natural wonders become the main choice of tourists and the length of stay between 8-14 days. The main purpose of tourists visiting the TIC to get tourism information and transportation information. Whereas the tourist objects most favored by tourists are natural wonders and adventure wonders. Furthermore, the results of TIC service analysis show that physical environment quality, interaction quality, outcome quality affect service user satisfaction, while E-Technology quality does not affect service user satisfaction.